Explaining Vertical-Selective Policies in Export Policy of Iran - Hamed Farahmand Moein (سیاست نامه علم و فناوری, 2018)
The experience of industrial countries shows that over time, a country attempts to industrialize the ladder ladder as soon as possible, comparing the comparative advantage, that is from the state of the commodities of primary goods and goods that are dependent on natural resources, to the exporter of goods Which are affiliated with the workforce. In the next step, it will become an exporter of IT products and eventually become exporter of knowledgeable goods. This is despite the fact that Iran, given the high potential of highly skilled manpower, does not have much to contribute to the export of high tech products and know-how, or in other words, it has a comparative advantage in the lower steps. Therefore, the presence of Iran in the field of high-tech industries requires proper planning, adopting appropriate supportive policies, and in one word, requires a vertical-selective policy in accordance with different time horizons. Vertical-selective policies are a set of measures in the short, medium, and long-term horizons of export goods and major export destinations. Therefore, the country must have measures that can be used to grow its currency and its continuity, what goods to export to and which countries there are, or whether there are problems or problems and obstacles to their realization.